2004
DOI: 10.1016/j.chembiol.2004.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing a Correlation between siRNA Localization, Cellular Uptake, and RNAi in Living Cells

Abstract: RNA interference (RNAi) is the process by which short-interfering RNA (siRNA) target a specific mRNA for degradation through interactions with an RNA-induced silencing complex (RISC). Here, a clear correlation between siRNA localization, cellular uptake, and RNAi activity was discovered by delivering siRNA into cells using siRNA-TAT(47-57) peptide, siRNA-TAT(47-57)-derived oligocarbamate conjugates, or nanoparticles. For successful RNAi, the localization of siRNA was distinctly perinuclear, suggesting that siR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
247
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(265 citation statements)
references
References 52 publications
15
247
3
Order By: Relevance
“…Tat, TP, and penetratin covalently linked to siRNA against luciferase, and GFP showed internalization and downregulation of gene expression (86,87). It has been further suggested that the cellular uptake of siRNA can be enhanced by noncovalent packaging with CPPs (88).…”
Section: Delivery Of Nucleic Acids By Cpp-mediated Cargo Deliverymentioning
confidence: 99%
“…Tat, TP, and penetratin covalently linked to siRNA against luciferase, and GFP showed internalization and downregulation of gene expression (86,87). It has been further suggested that the cellular uptake of siRNA can be enhanced by noncovalent packaging with CPPs (88).…”
Section: Delivery Of Nucleic Acids By Cpp-mediated Cargo Deliverymentioning
confidence: 99%
“…However, the combined challenges of intracellular delivery and unintended ''off-target'' effects remain formidable (4). The polyanionic nature and molecular size of siRNA are impediments to their entry into mammalian cells (5)(6)(7). In addition, siRNAs have both sequence-specific (8 -10) and sequence-independent (11-13) off-target effects, some of which are better understood than others.…”
mentioning
confidence: 99%
“…1, location of siRNA in perinuclear site showed that siRNA has entered the cells. Location in perinuclear site was correlated with the efficacy of RNAi [12].…”
Section: B Activation Of Crebmentioning
confidence: 99%
“…RNAi CREB is a process where intracellular pathway activation modulated by small-interfering RNA (siRNA) consisted of 21-23 nucleotides induces the degradation of specific mRNA target [12]. In Fig.…”
Section: B Activation Of Crebmentioning
confidence: 99%